TINGKAT KEPENTINGAN DAN KEPUASAN WISATAWAN AUSTRALIA TERHADAP PELAYANAN GARUDA INDONESIA PADA RUTE PENERBANGAN LANGSUNG AUSTRALIA-BALI - Magdalena Massenga, SE., MM (Institut Pariwisata dan Bisnis Internasional, 2014)
The growth of tourism sectors in Bali offers prospected bussinws opportunities to Garuda Indoninesia aircraft provides air transportation services from/to their homeland. As Australian tourist market is the biggest market in Bali, this study aims to explore the services performance, level of important factors of service performance of Garuda Indonesia at direct flight Australia –Bali route.Total 56 respondents contribute in this study which departed from several airport in Perth, Sydney, Tullamarine (Melbourne), Canberra, Adelaide, and Brisbane to Bali. Important-Performance Analysis used as approch in this study based on the recommendation of previous study by Martilla and James (1977). Service attributes measured in this study adopted from Garuda Indonesia service attributes which consist of 1) On Time Performance, 2) Website Service (www.garuda-indonesia.com), 3) Call Centre Service, 4) Sales Office Service, 5) Ticketing service at Airport, 6) Customer Service Desk, 7) Check-in service, 8) Arrival Assistance & Transfer Desk, 9) Executive Lounge Garuda, 10) Boarding Management, 11) In Flight Sales, 12) Cabin Crew Service, 13) Cabin Condition (Ambience & Cleanliness), 14) Seat Comfort, 15) Lavatory Cleanlines & Function), 16) Food & Beverage (Quality & Quantity), 17) In Flight Entertainment (Audio Video & Reading Material), 18) Cabin Amenity (Blanket, Towel, Pillow, Toilet Kit), 19) Baggage Service, 20) Complaint Handling, 21) Loyalty Program (for Frequent Flyer Program), 22) Overall Staff Greeting & Announcement.Research finding shows that there were 11 service attibutes catagorized as very important attributes, 11 others attributes catagorized as less important attributes, 19 service attributes performance met passengers expectation, and 3 attributes under passengers expectation.This study recommends Garuda Indonesia Management to retain service attribute’s performance which classified as in Quadran B, and ignores service attributes performance which classified as in Quadran D because of over valued by passengers.